Fascism, Violence, and Italian Colonialism. Issue 1 (1st January 2019) - Finaldi, Giuseppe
ABSTRACT: The foundations of Italy's colonial empire in Africa were laid when Italy was an aspirational and well-meaning liberal nation. In the 1920s and 1930s, like its predecessor, Mussolini's Fascist state also looked to Africa to expand. Focusing on the Italian reconquest of Libya in the late 1920s and early 1930s, as well as the brutal massacre of civilians that took place in Ethiopia in 1937, this article looks into the nature of Italian colonial violence and asks what difference Fascism made. Looking back at the Italian massacre of Libyans in Tripoli in 1911 as well, it argues that Fascism did not so much turn Italians into Mussolini's 'willing executioners' – though they did indeed kill willingly in Africa – but rather that the regime succeeded in removing certain factors, such as free press and political plurality, which had been present in the liberal era and had acted to restrain the use of unlimited violence in the colonial setting.